Sports as a tool for social development: How teamwork and competition shape children´s social skills - Bhimavarapu, M. (European Journal of Educational and Development Psychology, 2025)
Sports participation provides children with essential opportunities for social development beyond physical skills. This article explores how organized sports function as natural laboratories where children develop critical social competencies under adult guidance. Through structured engagement in sports, children acquire communication abilities, teamwork skills, conflict resolution strategies, and leadership capabilities that transfer to broader social contexts. It examines theoretical frameworks explaining sports` developmental impact, including Social Learning Theory, Social Development Theory, and the Positive Youth Development Model. It analyzes specific psychological mechanisms underlying social growth, including self-regulation, perspective-taking, and identity formation. It highlights how structural elements of sports—rules, adult mentorship, and progressive challenge—create optimal conditions for social learning. The article concludes with evidence-based recommendations for program design and coach training to maximize positive social outcomes while mitigating potential negative experiences. It demonstrates that when properly structured, sports participation represents a powerful tool for fostering children`s social development, with benefits extending far beyond the playing field.